Uncovering the role of tumor cGAS expression in predicting response to PD-1/L1 inhibitors in non-small cell lung cancer - Yuichi Ozawa; Yasuhiro Koh; Ryota Shibaki; Yuhei Harutani; Hiroaki Akamatsu; Atsushi Hayata; Takeya Sugimoto; Yuka Kitamura; Junya Fukuoka; Masanori Nakanishi; Nobuyuki Yamamoto (Cancer Immunology, Immunotherapy)
Abstract Objectives The impact of cGAS/STING tumor expression on PD-1/L1 inhibitor efficacy and the tumor microenvironment remain to be elucidated. Methods In a post-hoc analysis of a prospective biomarker study with 106 advanced NSCLC patients treated with PD-1/L1 inhibitors from December 2015 to September 2018, tumor tissue before treatment from 68 patients was analyzed. cGAS and STING expression were measured using immunohistochemical staining and H-scores. Additionally, 40 serum proteins were quantified before and 4–6 weeks after treatment initiation. Results Median cGAS and STING H-scores were 220 (range, 5–300) and 190 (range, 0–300), respectively. There were no differences in cGAS or STING H-scores between the high (tumor proportion score [TPS] ≥ 50) and low (TPS < 50) PD-L1groups (p = 0.990 and 0.283, respectively). Unexpectedly, patients with high cGAS (H-score ≥ 220) demonstrated significantly shorter progression-free survival (PFS) of PD-1/L1 inhibitors when the PD-L1 TPS was high (median PFS: 143 days vs. not reached; p = 0.028); PFS at 18 months was 7% and 53% in the high and low cGAS groups, respectively while STING expression did not impact PFS. In serum protein analyses, high cGAS H-score was associated with significantly higher TGF-β1 and TGF-β2 before PD-1/L1 inhibition (47.5 vs. 22.3 ng/l, p = 0.023; 2118 vs. 882 pg/ml, p = 0.037); additionally, the cGAS H-score significantly correlated with TGF-β1 (r = 0.451, p = 0.009) and TGF-β2 (r = 0.375, p = 0.031) basal levels. Conclusion cGAS expression, but not STING, predicts poor PD-1/L1 inhibitor efficacy in NSCLC with high PD-L1, potentially due to a TGF-β-mediated immunosuppressive environment (UMIN000024414).